Um estudo sobre o ciclo de vida do periódico Psicopedagogia - Revista da Associação Brasileira de Psicopedagogia (1982 2006) - Nemitz, Marcos Daniel (2009)
This work was based in the psycho pedagogy periodical Brazilian Association Magazine of Psycho pedagogy, in the period 1982 2006. The periodical was considered the printed matter representative of the Brazilian Psycho pedagogy history, mostly because of the important role that is has played in the formation process of the psycho pedagogies and in the Psycho pedagogy as knowledge area in the Education field. In this research was used as theoretical reference Pierre Bourdieu s concept of field. This author understands field as a space in which it is established a competition relation. The dispute in this competition is the one for the authority monopolization and the scientific knowledge about the theme (Bourdieu, 1983). This research aim is the understanding of the printed matter as strategy for the constitution of the Psycho pedagogy as study area inside the Education field. The periodical is taken as research object and is been analyzed as dispositive to normatize the Psycho pedagogy practice, at the same time it is considered as a material support that permits to amplify the discussion within the Education field from a Psycho pedagogical point of view